2018
DOI: 10.2308/accr-52003
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study on Small Accounting Firm Membership in Associations and Networks: Implications for Audit Quality

Abstract: Small accounting firms represent important participants in the audit market, yet details of how they operate and develop competencies remain unexplored. Small firms often join forces through accounting associations and networks (AANs), which may help them overcome significant challenges commonly faced by smaller firms. We interview 37 partners from 18 firms representing nine AANs to examine how small firms leverage their AAN membership and to understand the related implications for audit quality. Our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Given the fact that auditors perceive it as aggressive, this will ultimately cause greater proposed adjustment on an unrelated audit difference (Commerford et al 2018). The empirical study conducted by Bills et al (2018) indicated that small firms use accounting associations and networks resources as expertise, documenting that such demarche is critical to their audit quality. Also, the positive impact of social bonds on audits of complex estimates was documented by Kachelmeier and Van Landuyt (2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that auditors perceive it as aggressive, this will ultimately cause greater proposed adjustment on an unrelated audit difference (Commerford et al 2018). The empirical study conducted by Bills et al (2018) indicated that small firms use accounting associations and networks resources as expertise, documenting that such demarche is critical to their audit quality. Also, the positive impact of social bonds on audits of complex estimates was documented by Kachelmeier and Van Landuyt (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gerakos and Syverson, 2017) and three studies the interview (e.g. Cohen et al (2017); Bills et al (2018); Johed and Catasus (2018). Our discussion highlights that excepting the mathematical / statistical research method and experiment, other research methods are clearly underused.…”
Section: Table 1 Descriptive Data On Journal Articles On Auditing Rementioning
confidence: 93%
“…Audit pricing is a common concern of the company's internal financial and auditing industries, which is affected by various company characteristics such as company size and property rights. Customers will also set their own audit pricing according to their business development and operation, so there is a pricing game between the psychological price of customers and the audit pricing of accounting firms (Bills et al, 2018). The tripartite game participation methods, including the regulators such as the China Securities Regulatory Commission and the China Investment Association, are shown in Figure 1.…”
Section: Impact Of Customer Psychological Price On Audit Pricing In Smentioning
confidence: 99%
“…This study also examines the extent to which human capital development strategies are influenced by membership to an accounting association or network (AAN) where one of the perceived benefits cited among US small firms was access to joint conferences and technical training (Bills, Cunningham, & Myers, 2015). Studies have shown that membership to AAN lead to higher audit quality, and hence audit fee revenue (Bills, Walton, Hayne, & Stein, 2018;Mao, Qi, & Xu, 2017 The measure of the level of competitiveness of the SMPs based on total clients billed per annum is calculated using a maximum of 90 clients for each of the three business lines of audit/assurance, tax and consulting. This corresponds to 270 clients per annum.…”
Section: Variables Descriptionmentioning
confidence: 99%